HARMONIC MITIGATION USING SHUNT ACTIVE POWER FILTER BASED ON SYNCHRONOUS REFERENCE FRAME THEORY - Irdina Izzati, Abdul Harun (Universiti Malaysia Sarawak, (UNIMAS), 2023)
Harmonic distortion, arising from nonlinear loads in modern power systems, poses a significant power quality issue, deteriorating overall power quality and affecting sensitive equipment. Extensive research has been conducted to develop effective mitigation techniques, including filters, harmonic compensators, low harmonic drives, oversizing of neutral conductors, and power factor correction devices. However, tailored solutions are necessary due to the diversity of power sources, harmonics, and equipment. This project focuses on the design aspects of a three-phase Shunt Active Power Filter (SAPF) as an efficient harmonic mitigation device. The SAPF utilizes the synchronous reference frame theory and a hysteresis Proportional-Integral (PI) control algorithm to extract harmonic components and provide compensating currents. Extensive simulation analysis using MATLAB Simulink evaluates the SAPF's performance under different operating conditions, demonstrating its ability to restore distorted current waveforms and surpass the harmonic limits specified by the IEE-519 standards. The SAPF achieves a remarkable reduction in Total Harmonic Distortion (THD) through Frequency Fourier Transform (FFT) analysis. The successful implementation of the proposed filter and its superior harmonic mitigation capabilities represent significant advancements in power quality improvement, surpassing existing methods. The used of synchronous reference frame theory (SRF) for harmonic signal extraction holds promise for future developments in harmonic mitigation techniques.